MANAGEMENT PRACTICES OF SCHOOL HEADS AND WORK ETHICS OF PUBLIC ELEMENTARY SCHOOL TEACHERS IN DUMARAO DISTRICT - Gobuyan, Maybelle P.; Vasquez, Michael B; De Sales, Leonor D. (President University, 2024)
The study investigated the management practices of school heads and work ethics of public elementary school teachers in the District of Dumarao. The respondents of the study were 223 public elementary school teachers who were selected using random sampling method. The study used the descriptive-correlational research design. Data were collected using a researcher-made questionnaire. Statistical tools used to analyze and interpret data were frequency count, percentage, mean, t-test, and analysis of variance, and Pearson r. The results revealed the level of management practices of school heads and the degree of work ethics of public elementary school teachers were found to be “high”. There was no significant in the level of management practices of school heads and the degree of work ethics of public elementary school teachers when respondents were grouped according to status of age and length of service, while no significant differences were found when grouped according to sex and highest educational attainment. There was a significant relationship between the level of management practices of school heads and the degree of work ethics of public elementary school teachers